Group ACT for Psychological Flexibility and Emotion Regulation in ACEs Survivors - Shalsabilla, Hassya Noertalitha; Sari, Yudiana Ratna (Yayasan Mata Pena Madani, 2025)
Childhood abuse or Adverse Childhood Experiences (ACEs) can have long-term impacts on an individual's mental health and emotional regulation strategies. In Indonesia, cases of ACEs remain prevalent and continue to rise each year. Individuals with ACEs often struggle to accept their past and face emotional challenges in adulthood. This study aims to examine the effectiveness of Acceptance and Commitment Group Therapy in enhancing psychological flexibility and emotion regulation strategies in young adults with a history of ACEs. The sample consisted of individuals aged 18–30 years with ACEs who participated in four sessions of ACT-based group therapy. Data were collected using the Acceptance and Action Questionnaire-2 (AAQ-2) and the Cognitive Emotion Regulation Questionnaire (CERQ), and were complemented by qualitative interviews. Data analysis was conducted using the Repeated Measures ANOVA method. The results showed a significant decrease in psychological inflexibility scores following the intervention, while increases in positive emotion regulation strategies and decreases in negative strategies were not statistically significant.